Day‐to‐day variability of foEs in the equatorial ionosphere. Issue 5 (13th September 2013) - Somoye, E. O.; Akala, A. O.; Adeniji‐Adele, R. A.; Onori, E. O.; Ogwala, A.; Karimu, A. O.
Abstract [1] Diurnal, seasonal, and solar cycle effects of the variability (VR) of the critical frequency of sporadic E layer (foEsq) are investigated at Ibadan (7.4°N, 3.9°E, 6°S dip) in the African sector during high solar activity (HSA) year of 1958 (Rz = 181), moderate solar activity (MSA) year of 1973 (Rz = 30), and low solar activity (LSA) year of 1965 (Rz = 17). The diurnal variation of foEsq VR is characterized by post‐midnight (32%–78%) and pre‐midnight (20%–84%) peaks during high solar activity (HSA), the only epoch of the three showing these peaks and a diurnal trend. While the daytime foEsq VRs of the three epochs show no seasonal trend, pre‐midnight and post‐midnight, the foEsq VRs during HSA and LSA show seasonal trends. Similarity is observed in the curve of reciprocal of percentage occurrence of Esq and that of foEsq VR, indicating inverse variation of percentage occurrence and foEsq VR. Longitudinal influence is observed in the diurnal variation of HSA and MSA July foEsq VR of Ibadan (7.4°N, 3.9°E, 6°S dip) in the African sector, which is in the neighborhood of the Greenwich Meridian (GM); Singapore (1.3°N, 108.3°E, 17.6°S dip) in the Asian sector, east of GM; and Huancayo (12°S, 284.7°E, 1.90 dip) in the American sector, west of GM.